2021
DOI: 10.1101/2021.07.15.21260589
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preventable deaths from SARS-CoV-2 in England and Wales: a systematic case series of coroners’ reports during the COVID-19 pandemic

Abstract: As of June 2021, 12% of global deaths attributed to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have occurred in England and Wales. Examining Coroners Prevention of Future Deaths reports (PFDs) between March 2020 and 28 June 2021 in England and Wales, we found 23 cases (4.5% of PFDs) involving SARS-CoV-2, with 52% (n=12) of deaths indirectly- and 48% directly-related. There was geographical variation with most (39%) PFDs written by coroners in the North-West of England. Fifty-six concerns … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…Our research, alongside other studies (10,12,24,34,3843), highlights that PFDs contain a wealth of important information that has merit for wide dissemination. However, crucial information in PFDs is often missing, incorrect, or inconsistent.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our research, alongside other studies (10,12,24,34,3843), highlights that PFDs contain a wealth of important information that has merit for wide dissemination. However, crucial information in PFDs is often missing, incorrect, or inconsistent.…”
Section: Discussionsupporting
confidence: 55%
“…This difference can be attributed to the quality of our data collection methods, which allowed us to examine all available PFDs to which medicines contributed. Compared with previous studies (10)(11)(12)24,34), concerns reported by coroners were the same, except for those relating to patient safety, which has not been identified in PFDs before. However, in a study examining hospital incident reports, 18% of concerns were related to patient safety (35).…”
Section: Comparison With Previous Literaturementioning
confidence: 55%
“…30 Fortunately, the value of PFDs as a tool for improving clinical practice is being recognised, and efforts are underway to widely disseminate their lessons to healthcare professionals, policymakers, and the public. 31 36 …”
Section: Discussionmentioning
confidence: 99%
“…We extracted a series of cases from the Courts and Tribunals Judiciary website and analysed them according to a study protocol that was preregistered on an open repository 16…”
Section: Methodsmentioning
confidence: 99%